AN ANALYSIS OF ENGLISH DEPARTMENT STUDENTS' ABILITY IN WRITING ARGUMENTATIVE ESSAY - Yesi Fitriani; Mulyadi Mulyadi; Fernandita Gusweni Jayanti (Universitas Galuh, 2019)
The purpose of this research is to describe the English Department students' ability in writing an argumentative essay. The research is designed as a descriptive quantitative method. The population of the research is the fourth semester students of English Department at Universitas Bengkulu in academic year 2018/2019. This research used random sampling technique in deciding the sample. The samples were 26 students. The students were asked to write an argumentative essay within 100 minutes. The students writings were analyzed by using assessment rubrics adapted from Schwalm (2007) and Jacobs et.al (1981) which consists of introduction, body paragraph, conclusion, language use, and mechanics. The result shows that students ability in writing argumentative essay is fair. From the final scores it could be seen that there was one student (3.8%) got very good grade, then 11 students (42.3%) got good grade, the most of the students or 12 students (46.2%) got fair grade, the rest of them or 2 students (7.7%) got poor grade. Keywords: analysis, writing, argumentative essay